Fundamentalismo político de Jair Bolsonaro: a percepção antiestablishment do bolsonarismo - Amorim, Fabricio Augusto Antonio (2024)
This work enters the universe of Bolsonarism. Initially, we use the concept of political fundamentalism, transposed from theology, in order to understand how Jair Bolsonaro captures the truth and nullifies the possibility of dialogue so fundamental in a democracy, and then observe how he uses disinformation techniques in communicating with his followers and in attacks on institutions. In a second step, we seek to understand how Bolsonarists receive the populist dynamics and political fundamentalism. To this end, we carried out in-depth online interviews with Bolsonaro supporters and occasional voters of Jair Bolsonaro in the 2022 electoral period, in the city of São Paulo, and verified their perception of the mainstream media, institutions such as the Supreme Court and the Electoral Court, electoral system, in addition to the conception they constructed about Jair Bolsonaro's performance in the Covid-19 pandemic and his government. Bolsonarists validate and legitimize the message produced by Jair Bolsonaro. We see that for them the truth is found in Bolsonaro, that we are living in a fight between good and evil, in which evil is the establishment, and that it is therefore necessary to rebuild the democracy destroyed by our enemies